Pengaruh Literasi Keuangan dan Kemudahan Penggunaan terhadap Keputusan Penggunaan Shopeepay pada Mahasiswa D4 dan S1 Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta - Angella Priyatna; Atika Siti Hajar; Gemah Putri Djaelani; Nabila Ramadhanti; Umi Widyastuti; Destria Kurnianti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study examines the influence of financial literacy and ease of use on the decision to use ShopeePay among undergraduate and diploma students of the Faculty of Economics and Business at the State University of Jakarta. A quantitative research method was applied through a survey of 151 respondents selected using purposive sampling. Data were collected via an online questionnaire and analyzed using multiple linear regression. The results of the study indicate that financial literacy and ease of use have a positive and significant effect on the decision to use ShopeePay, both partially and simultaneously. Financial literacy enhances students’ ability to manage finances and make prudent financial decisions. Ease of use encourages comfort in adopting financial technology. The independent variables explain 35.6% of the variability in the decision to use ShopeePay, while the remaining portion is influenced by other factors. This research supports the literature on financial technology adoption and contributes to marketing strategies and financial education for digital wallet providers.